Constance Beresford-Howe's interrogation of integrative feminism. - Gale, Heather. (University of Ottawa (Canada), 1994)
This thesis analyzes Constance Beresford-Howe's novels in terms of their place in the contemporary feminist debate over women's traditional roles as mothers, daughters, sisters, and wives. Her treatment of these roles supports Andrea O'Reilly's assertion that Beresford-Howe espouses what Angela Miles has called "integrative feminism", "a feminism which affirms and celebrates women's specificity and asks not for the eradication of women's traditional roles and values but for the recognition of their importance" (O'Reilly 69). Chapter One deals with a range of feminist literary criticism and particularly with the notion of "integrative feminism" and its applicability to the novels of Beresford-Howe, as well as entertaining complementary and divergent readings of this theory offered by such critics as Germaine Greer and Judith Stacey. Chapter Two considers the portrayal of sisters, daughters, and other female "helpers" in such novels as Of this Day's Journey (1947), The Invisible Gate (1949), My Lady Greensleeves (1955), A Population of One (1977), and Prospero's Daughter (1988). Chapter Three examines the portrayal of the institutionalized roles of mother and wife in such novels as The Unreasoning Heart (1946), My Lady Greensleeves 1955), The Book of Eve (1973), and Night Studies (1985). Chapter four extends the discussion of mothers and wives, with an emphasis on the protagonist's successful redefinition of those roles in The Marriage Bed (1981) and A Serious Widow (1991).
Keywords: Literature, Modern.